The Challenges of Enforcing the Police Code of Ethics in the Ethical Tribunal Procedures for Police Officers - Donny Widianto; Suparno Suparno (Yayasan Adra Karima Hubbi, 2024)
Police code of ethics law enforcement is a crucial aspect in creating a police institution that is professional, accountable, and trusted by the public. This article discusses the problems faced in the procedure for the code of ethics trial for Polri members, with a focus on the law enforcement mechanism for violations of the professional code of ethics in the police. Although there is a clear regulatory framework, including Police Regulation Number 7 of 2022, the implementation of the code of ethics trial is often marred by a lack of transparency and accountability. The trial, which is carried out behind closed doors, results in public distrust of the integrity of the law enforcement process. In addition, the sanctions imposed are often considered disproportionate to the severity of the violation, creating the impression that violators can avoid more severe consequences. This study also highlights other issues that arise, such as the overlap between the code of ethics trial process and criminal justice, as well as the neglect of victims' rights in the legal process. By analyzing these problems, this study provides an effort for the necessary reforms in the Polri Code of ethics and law enforcement mechanism to ensure justice and accountability and increase public trust in the police institution.